[1,3]-Dioxolo[4,5-f]benzodioxole (DBD) Fluorescent Dyes; Synthesis, Properties, and Applications - Wessig, Pablo; Lehmann, Max (Synthesis, 2023)
In this review we give an overview of the syntheses and photophysical properties of the new class of fluorescent dyes based on a [1,3]-dioxolo[4,5-f]benzodioxole core and their derivatives. Starting from commercially available reactants (e.g., sesamol, 1,2,4,5-tetrachlorobenzene) the core units can be prepared in a simple manner. Then, the benzene core can be derivatized via lithiation and their photophysical properties can be adjusted as desired. The obtained fluorophores have an absorption range of 403–520 nm and an emission range of 495–665 nm. This class of fluorescent dyes is also characterized by a long fluorescence lifetime, a high stability towards photobleaching, large Stokes shifts, and small size. Thus, the DBD dyes are optimally suited for optical sensing.1 Introduction2 Synthesis3 Properties4 Applications
Keywords: fluorescent dyes; heterocycles; photophysics; Stokes shift; probes; FRET